Re-expansion of vertebral compression fractures in patients with multiple myeloma with percutaneous vertebroplasty using spinejack implants: a preliminary and retrospective study - Pusceddu, Claudio; Faiella, Eliodoro; Derudas, Daniele; Ballicu, Nicola; Melis, Luca; Zedda, Stefano; Marsico, Salvatore (Frontiers in Surgery, 2023)
Objective: To retrospectively evaluate the feasibility and effectiveness of vertebroplasty using Spinejack implantation for the treatment and stabilization of painful vertebral compression fractures, in patients diagnosed with Multiple Myeloma (MM), to allow both an effective pain reduction and a global structural spine stabilization. Results: The technical success rate was 100%. No procedure-related major complications or death occurred. In the 6-month follow-up, the mean VAS score decreased from 5.4 ± 1.0 to 0.2 ± 0.5 with a mean reduction of 96.3%. FMS FMS decreased from 2.3± 0.5 vs 1.2 ± 0.4 with a mean reduction of -47.8%. There were no major complications related to incorrect positioning of the Expandable Titanium SpineJack Implants. In five patients, a cement leak was observed with no associated clinical manifestations. The average length of hospital stay was 6-8 Hours6.6 ± 1.2 hours. No new bone fractures or local disease recurrence occurred during a median contrast-enhanced CT follow-up of 6 months. Conclusions: our results suggest that vertebroplasty, using Spinejack implantation for the treatment and stabilization of painful vertebral compression fractures, secondary to Multiple Myeloma is a safe and effective procedure with long - term pain relief and restoration of vertebral height.